PERAN PENYULUHAN HUKUM KELUARGA ISLAM DALAM PEMBERDAYAAN MASYARAKAT UNTUK PENCEGAHAN PERNIKAHAN DINI DI PAGAR DEWA - Juanda, Anugrah; Sibuea, Sumayya Febrianti Sukma; Utami, Utami; Dita, Tiara; Anggraeni, Fenty; Yarmunida, Miti (CV. Kalimasada Group, 2025)
In 2024, Bengkulu Province recorded the highest prevalence of early marriage in Sumatra, reaching 21.1%. This issue is particularly pressing in Pagar Dewa Subdistrict, Selebar District, Bengkulu City. This study aims to analyze the role of Islamic family law counseling in enhancing legal awareness among adolescents as a preventive measure against early marriage. The counseling activities were carried out by students participating in the KKN MBKM (Independent Campus) program from the Islamic Family Law Department, Faculty of Sharia, UIN Fatmawati Sukarno Bengkulu. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, focus group discussions (FGDs), and participatory observation. Participants were selected purposively, focusing on adolescents aged 13–19 from diverse socio-economic backgrounds. The findings indicate that legal counseling based on religious values and effective communication significantly improved adolescents' understanding of the negative impacts of early marriage. This improvement was evident from increased post-test scores compared to pre-test results, along with high engagement in group discussions. The use of interactive learning media proved effective in fostering critical awareness among adolescents regarding the importance of education and reproductive health as foundations for their future.